Business ethics: an Indian perspective - Fernando,A C. (Dorling kindersley, 2014)
Business Ethics: An Indian Perspective provides a comprehensive coverage of the theories of business ethics and emphasizes the importance of ethical principles in overcoming moral dilemmas in the business world. Using a large number of India-centric case studies and examples, this book helps readers develop the reasoning and analytical skills needed to apply ethical concepts to business. The coverage on the ethical theories underlying business and their application in the real world, a special focus on ethical issues in consumer protection and the information technology sector and whistle-blowing makes this revised edition highly relevant for students today.